How Should We Organize Care for Patients With Human Immunodeficiency Virus and Comorbidities? A Multisite Qualitative Study of Human Immunodeficiency Virus Care in the United States Department of Veterans Affairs. Issue 8 (23rd August 2021) - Bokhour, Barbara G.; Bolton, Rendelle E.; Asch, Steven M.; Dvorin, Kelly; Fix, Gemmae M.; Gifford, Allen L.; Hyde, Justeen K.; McInnes, D. Keith; Parker, Victoria A.; Richardson, Kelly; Skolnik, Avy A.; Vaughan-Sarrazin, Mary S.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: With human immunodeficiency virus (HIV) now managed as a chronic disease, health care has had to change and expand to include management of other critical comorbidities. We sought to understand how variation in the organization, structure and processes of HIV and comorbidity care, based on patient-centered medical home (PCMH) principles, was related to care quality for Veterans with HIV. Research Design: Qualitative site visits were conducted at a purposive sample of 8 Department of Veterans Affairs Medical Centers, varying in care quality and outcomes for HIV and common comorbidities. Site visits entailed conduct of patient interviews (n=60); HIV care team interviews (n=60); direct observation of clinic processes and team interactions (n=22); and direct observations of patient-provider clinical encounters (n=45). Data were analyzed using a priori and emergent codes, construction of site syntheses and comparing sites with varying levels of quality. Results: Sites highest and lowest in both HIV and comorbidity care quality demonstrated clear differences in provision of PCMH-principled care. The highest site provided greater team-based, comprehensive, patient-centered, and data-driven care and engaged in continuous improvement. Sites with higher HIV care quality attended more to psychosocial needs. Sites that had consistent processes for comorbidity care, whether in HIV or primary care clinics, had higher quality of comorbidity care. Conclusions: Provision of high-quality HIV care and high-quality co-morbidity care require different care structures and processes. Provision of both requires a focus on providing care aligned with PCMH principles, integrating psychosocial needs into care, and establishing explicit consistent approaches to comorbidity management.